2020
DOI: 10.20450/mjcce.2020.2025
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a new conjugated polymer containing bithiazole group and its thermal decomposition kinetics

Abstract: A new conjugated polymer containing a bithiazole group is prepared by the polycondensation of 2,2'-diamino-4,4'-bithiazole and terephthaldialdehyde in the presence of glacial acetic acid. The kinetics of thermal degradation of the new polymer are investigated by thermogravimetric analysis at different heating rates. The temperature corresponding to the maximum rate loss shifts to higher temperatures with increasing heating rate. The thermal decomposition activation energies of the conjugated polymer in a conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…The clear observability of characteristic bands in the amide monomer and the absence of alkene bands in the monomers show that our newly synthesized polymer has formed and the literature also support this allegation (Coşkun et al, 2002;Kurt et al, 2019a). Actually, the FT-IR spectrum is the first spectroscopic measurement method that shows us whether newly synthesized materials are formed or not, and has been used in the literature for many years (Turan & Şekerci, 2009;Temüz, 2017;Coşkun et al, 2019;Kurt et al, 2020).…”
Section: Spectroscopic Characterization Of Lim-co-npa Copolymersupporting
confidence: 60%
“…The clear observability of characteristic bands in the amide monomer and the absence of alkene bands in the monomers show that our newly synthesized polymer has formed and the literature also support this allegation (Coşkun et al, 2002;Kurt et al, 2019a). Actually, the FT-IR spectrum is the first spectroscopic measurement method that shows us whether newly synthesized materials are formed or not, and has been used in the literature for many years (Turan & Şekerci, 2009;Temüz, 2017;Coşkun et al, 2019;Kurt et al, 2020).…”
Section: Spectroscopic Characterization Of Lim-co-npa Copolymersupporting
confidence: 60%
“…Similar results for thermal degradation of heterocyclic polymers have been reported in our previous publications and also by different researchers. [34][35][36][37][38][39][40][41][42] For example, Kurt et al 37 reported the degradation temperatures of an isocoumarin derived polymer changed in a positive direction, which increased 256.6 °C to 286.1 °C by increasing heating rate from 5 to 20 °C/min. Meng and friends investigated the thermal degradation kinetics of a polyimide polymer containing 2,6-benzobisoxwwwwazole units and reported the onset decomposition temperatures increased with increase of heating rates.…”
Section: Resultsmentioning
confidence: 99%